EFFECT OF DOSAGE OF PGPR (Plant Gowth Promoting Rhizobacteria) Eleusine indica (L.) Gaertn ROOTS ON GROWTH AND YIELDS OF Asystasia gangetica (L.) subsp. Micrantha ON DIFFERENT SOIL TYPES - S. M., Ramadhanti; Wirawan, I W.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
PGPR activities have a positive impact on increasing forage crop yields to protect root caps and improve the environment by reducing the use of inorganic fertilizers. The study aimed to determine the effect of Plant Growth Promoting Rhizobacteria dose of (Eleusine indica (L.) Gaertn) roots on the growth and yield of Asystasia gangetica (L.) subsp. Micrantha on different soils. The research was conducted at the Sesetan Research Station, Faculty of Animal Husbandry, Udayana University, Jalan Raya Sesetan, Denpasar. The study lasted for two months, using a completely randomized design with a split plot Pattern consisting of 3 types of soil (mediterranean, latosol, regosol) as the main plot and 3 levels of PGPR doses (0, 10 and 20 ml/liter air of water) as subplots. The variables observed were growth variables, yield variables and growth characteristic variables. The results showed that in all treatments, there was no interaction between soil type and PGPR doses except for the number of leaves variable and branches variable. The PGPR doses of 10 - 20 ml/liter air of water using Pengotan soil had high growth and yield of Asystasia gangetica forage plants. Growth and yield as well as plant growth characteristics showed better performance on Pengotan soil compared to Bukit and Sobangan soil. The conclusion of this study is that the additional dose of 10 – 20 ml/l can increase the growth and yield of Asystasia gangetica. The average regosol soil type produces the growth and yield of Asystasia gangetica which is better than Mediterranean soil and Latosol soil.